IMPLEMENTASI KEBIJAKAN KARTU IDENTITAS ANAK (KIA) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SAMARINDA - Faujiah, Noormila; Arifin, Muhammad Zainal (Journal of Policy & Bureaucracy Management, 2021)
The state is obliged to provide protection for children for their human rights, one of which is having identity recorded in state documents. This study aims to describe and analyse implementation of the Child Identity Card (CIC) policy at the Departement of Population and Civil Registration of Samarinda City, and identify the inhibiting factors. This study used descriptive qualitative method with a research focus, namely CIC communication, utilization of CIC, implementors involved and bureaucratic structure and inhibiting factors in its implementation. The results showed that implementation of the CIC policy at the Departement of Population and Civil Registration of Samarinda City has not yet been implemented optimally because there are still some obstacles in its implementation. In terms of communication, the provision of CIC socialization is still minimal and the number of CIC issuances is still far behind the number of children aged 0-16 years in Samarinda City, which means that there are still many children who have not registered for CIC. Then the use of CIC has not been felt as a whole by the community because of ignorance and the use of CIC through collaborative effeorts with business partnerships in providing shopping or recreational discounts have also not been realized as expected due to the Covid-19 pandemic. Even in terms of implementers and the bureaucratic structure is already well done.